Inclusive Pedagogical Practice as a Predictor of Quality Early Childhood Education - Ivana Visković* (RU Publications, 2021)
The quality of the educational process within the humanistic concept and holistic-developmental approach is interpreted as the optimal adaptation to the individual needs and abilities of children, while inclusiveness presupposes equal inclusion and participation of all children. This article explores the opinions of teachers as bearers of pedagogical-educational process. The aim of this research was to determine how much importance teachers attach to certain dimensions of the educational process, and the procedures of inclusive practice. Empirical research included teachers in 5 preschool institutions (N=146). The research instrument was constructed based on relevant literature. Teachers in this sample recognize the importance: of individualized support to all children; of respecting the diversity; of collaboration with parents, and personal professional development. At the same time, the level of formal education and in-service teacher training is positively correlated with the assessment of importance towards child-oriented practice, and respect for diversity. Teachers with a higher level of education significantly value the importance of additional vocational training in the field of developmental and social risks, the use of community resources, and involvement of parents in planning individual support for children.